Investigation of Cytomegalovirus in Intestinal Tissue in a Country With High CMV Seroprevalence - Hazır-Konya, Hande; Avkan-Oğuz, Vildan; Akpınar, Hale; Sağol, Özgül; Sayıner, Arzu (Turkish Journal of Gastroenterology, 2021)
Background: In Turkey, cytomegalovirus (CMV) seropositivity has been reported to be high, between 85 and 100%. CMV has been responsible for disease exacerbation in inflammatory bowel disease (IBD). We aimed to evaluate the presence of CMV in intestinal tissue by immunohistochemical staining in IBD and non-IBD patient groups, in a country with high CMV seroprevalence. Methods: In this prospective cross-sectional study, the presence of intestinal CMV was investigated with tissue immunohistochemistry (IHC) staining, which is accepted as the gold standard method, and with polymerase chain reaction (PCR) in tissue and blood. Patients (≥18 years old, n = 189) who had a colonoscopic biopsy between January and May 2017 were included in the study at our hospital. Clinical, laboratory, endoscopic, and histopathological data of patients were assessed by dividing them into IBD (n = 34) and non-IBD (n = 155) groups. Results: In this study, 567 colonic biopsy samples from 189 patients were evaluated. Tissue IHC staining was positive for 3 (1.58%) non-IBD patients. One of them was diagnosed as CMV ileitis. CMV DNA was also detected in 14 plasma (7.40%, <80-469 copies/mL) and 20 tissue samples (10.69%, 7-15 289 copies/mL). Tissue IHC staining is accepted as the gold standard for CMV ileitis, and the sensitivity and specificity of tissue PCR was 33% and 89.67%, while the sensitivity and specificity of plasma PCR was 66.66% and 93.54%, respectively. Conclusion: Although CMV seroprevalence is high in Turkey, CMV ileitis was diagnosed in only one non-IBD patient (0.53%). Compared to tissue IHC staining, the sensitivity of tissue and blood CMV PCR was low while their specificity was higher.